Staying Blind to Child Abusers: Comparing Child Protection Laws in South Korea and the US - Seoyoon Eunice Yang (Technium Social Sciences Journal, 2020)
Although there has been steady global progress in improving child rights during the past few decades, domestic child welfare laws and related policies are still inadequate in the sense that they cause some abused minors to remain in the blind spots of legal protection. The primary purpose of this research is to compare and contrast the child protection laws in South Korea and the United States, endeavoring to investigate three different aspects of the subject matter: legal definitions of child abuse, enforcement of child neglect law, and the legal capacity of youth victims. The final aim of this paper is to provide suggestions on how both systems could learn from each other’s strengths, and thereby offer the future direction for designing promising laws that can prioritize the best interests of children.